Metal stents are safe and cost‐effective for preoperative biliary drainage in resectable pancreaticobiliary tumours. Issue 9 (26th July 2021) - Roberts, Andrew T.; Jaya, Joseph; Ha, Phil; Thakur, Udit; Aldridge, Oscar; Pilgrim, Charles H. C.; Tan, Eren; Wong, Enoch; Fox, Adrian; Choi, Julian; Liew, Danny; Le, Suong T. T.; et al.
Abstract: Backgrounds: To compare the complication rates and overall costs of self‐expandable metal stents (SEMS) and plastic stents (PS) in clinically indicated preoperative biliary drainage (PBD) prior to a pancreatoduodenectomy (PD). Methods: We conducted an Australian multicentre retrospective cohort study using the databases of four tertiary hospitals. Adult patients who underwent clinically indicated endoscopic PBD prior to PD from 2010 to 2019 were included. Rates of complications attributable to PBD, surgical complications and pre‐operative endoscopic re‐intervention were calculated. Costing data were retrieved from our Financial department. Results: Among the 157 included patients (mean age 66.6 ± 9.8 years, 45.2% male), 49 (31.2%) received SEMS and 108 received PS (68.8%). Baseline bilirubin was 187.5 ± 122.6 μmol/L. Resection histopathology showed mainly adenocarcinoma (93.0%). Overall SEMS was associated less complications (12.2% vs. 28.7%, p  = 0.02) and a lower pre‐operative endoscopic re‐intervention rate (4.3 vs. 20.8%, p  = 0.03) compared with PS. There was no difference in post‐PD complication rates. On multivariate logistic regression analysis, stent type was an independent risk factor of PBD complication (OR of SEMS compared to PS 0.24, 95% CI 0.07–0.79, p  = 0.02) but not for any secondary outcome measures. Upfront material costs were $56USD for PS and $1991USD for SEMS. Accounting for rates of complications, average costs were similar ($3110USD for PS and $3026USD for SEMS). Conclusion: In resectable pancreaticobiliary tumours, SEMS for PBD was associated with reduced risk of overall PBD‐related complications and pre‐surgical endoscopic reintervention rates and was comparable to PS in terms of overall cost. Abstract : Self‐expandable metal stents (SEMS) compared to plastic stents (PS) are associated with reduced overall rates and likelihood of PBD‐related complication. SEMS are comparable to PS in terms of overall costs.